2013
DOI: 10.1111/ctr.12126
|View full text |Cite
|
Sign up to set email alerts
|

Excellent outcome of living donor liver transplantation in patients with hepatopulmonary syndrome: a single centre experience

Abstract: We report one of the largest series of LDLT in HPS which has shown excellent results.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“… 90 , 91 In the same study, patients with a pretransplantation PaO 2 < 44 mmHg had significantly lower post-transplantation survival rates compared with those with a PaO 2 between 44 and 54 mmHg. 90 It may come to mind that living donor LT (LDLT) may be more suitable than deceased donor LT (DDLT) because of the advantages of immediate availability of graft and opportunity to stabilize patient before LT. 86 However, some reports have shown that complication rates are the same between LDLT and DDLT patients. 92 95 To improve survival after LT, patients who are on the waiting list should be screened properly, and adequate oxygen should be given.…”
Section: Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“… 90 , 91 In the same study, patients with a pretransplantation PaO 2 < 44 mmHg had significantly lower post-transplantation survival rates compared with those with a PaO 2 between 44 and 54 mmHg. 90 It may come to mind that living donor LT (LDLT) may be more suitable than deceased donor LT (DDLT) because of the advantages of immediate availability of graft and opportunity to stabilize patient before LT. 86 However, some reports have shown that complication rates are the same between LDLT and DDLT patients. 92 95 To improve survival after LT, patients who are on the waiting list should be screened properly, and adequate oxygen should be given.…”
Section: Treatmentmentioning
confidence: 99%
“… 84 , 88 However, some other studies showed that there were no significant differences in survival between any HPS and non-HPS patients. 86 , 89 Iyer et al . reported that there was no association between PaO 2 levels at diagnosis and survival rates after transplantation.…”
Section: Treatmentmentioning
confidence: 99%
“…Only a few case series exist of LDLT in this setting and the largest describes 14 patients with excellent results. 10 They found that the overall time to extubation was 2 (1-32 days) and hospital stay was 20 (17-46 days). However, the length of time of normalization of arterial hypoxemia post LT is highly variable.…”
Section: Discussionmentioning
confidence: 99%
“…LT is the only cure for HPS, and the outcome of patients after LT is generally good . In one report, Saigal et al . reported 100% survival in patients with HPS after LT.…”
Section: Introductionmentioning
confidence: 99%